ETIKA KOMUNIKASI ISLAM DALAM KAJIAN SURAT AL-QASHASH AYAT 14-19: RELEVANSI UNTUK ERA MODERN - Nurdin, Hanifah; Azman Sulaiman; Fitri Meliya Sari; Zainal Arifin (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The Qur'an as the main source of Islamic communication science studies has verses that teach communicators and communicants in communicating. The Qur'an teaches how communicators build relationships with Allah and human kind, known as hablumminallah and hablumminannas. The success of communication is determined by how the communicator conveys the message. The delivery of the message must have ethics so that communication can take place properly. This research is a literature review that examines surah al-Qashash verses 14-19. In sura al- al-Qashash verses 14-19 Allah swt describes the story of Prophet Moses as in gaining prophetic wisdom. Verses that contain the ethics of Islamic communication with oneself, with Allah ta'ala and with man. This is where surah al-Qashash verses 14-19 become one of the foundations of the study of Islamic communication in ethics or morals.